Blended Problem Based-Learning: Enhancing speaking performance across self-efficacy levels - Lestari, Yunda; Hartono, Rudi; Yuliasri, Issy; Pratama, Hendi (TLEMC (Teaching and Learning English in Multicultural Contexts), 2025)
This study examines the effectiveness of the Blended Problem-Based Learning (Blended-PBL) approach in enhancing speaking performance among EFL students with different self-efficacy levels and explores students’ perceptions of its application in speaking instruction. Employing a quasi-experimental design, the research involved 32 undergraduate students of an English Education Study Program, consisting of 16 students with high self-efficacy and 16 with low self-efficacy, who participated in a speaking course during the 2023/2024 academic year. Data were collected through pre- and post-test speaking performance assessments evaluated with an analytic rubric, a self-efficacy questionnaire, and a perception survey, and analyzed using paired sample t-tests and descriptive statistics. The results indicated a significant improvement in students’ speaking performance after the Blended-PBL intervention, with a paired sample t-test yielding a value of t = -12.162 (p 0.05), confirming that the gains were statistically significant. Interestingly, although students with high self-efficacy performed slightly better than their peers with lower self-efficacy, the difference between the two groups was not statistically significant, suggesting that Blended-PBL is equally beneficial across varying levels of self-efficacy. Furthermore, perception data demonstrated that students held favorable views toward Blended-PBL, particularly in terms of motivation, collaboration, confidence building, and problem-solving skills. These findings highlight Blended-PBL as an effective and inclusive pedagogical model for EFL speaking instruction, with potential to foster learners engagement, reduce performance gaps, and promote a more supportive and equitable language learning environment.Keywords: Blended problem-based learning, self-efficacy levels, speaking performance